Pendampingan Pembuatan Rencana Anggaran Biaya Kantor Desa Persiapan Sama Guna Kecamatan Tanjung Kabupaten Lombok Utara - Ahmad Zarkasi; Adryan Fitrayudha; Heni Pujiastuti; Nurul Hidayati; Aulia Muttaqin; Maya Saridewi Pascanawati; Isfanari Isfanari; Erni Yustissiani; Hadi Rasikhun; Adiman Fariyadin; Dodik Kusumawanto; Syarifunnaji Ridho; Haidir Azim (Rengganis Jurnal Pengabdian Masyarakat, 2023)
Sama Guna Village is a burning village, according to North Lombok Regent Regulation Number 12 of 2015 and the Governor of West Nusa Tenggara Number 100/897/PEM. Sama Guna Village has obtained its operational rights to run the wheels of its organization. However, infrastructure facilities are still relatively minimal, as the office currently occupied is still on loan. The purpose of this service is to provide knowledge in making the budget plan required for the construction of the Sama Guna Village Office in accordance with PUPR Ministerial Regulation No. 1 of 2022. The method used is the presentation and discussion of PowerPoint slide media, which is then followed by assistance in making RAB. The activity took place on Wednesday, March 8, 2023, from 9.30 to 13.00 WITA, according to the agreement with the Head of the Sama Guna Village, in the meeting hall of the Sama Guna Village Office. This activity ran smoothly and in an orderly manner. During the implementation of the activity, the participants were very enthusiastic about participating in the activity; this was seen from the total number of participants, which reached more than 25 and was attended by the village head, devices, Babinsa, and the local community.